How frequent is bystander cardiopulmonary resuscitation performed in the community of Kota Bharu, Malaysia? - Chew, K S; Mohd Idzwan, Z; Nik Hishamuddun, N A R; Wan Aasim, W A; Kamaruddin, J (2008)
INTRODUCTION